1997
DOI: 10.1111/j.1600-0684.1997.tb00222.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of spontaneous congenital defects in rhesus and cynomolgus macaques

Abstract: This paper summarizes the spontaneous incidence of congenital defects in the rhesus and cynomolgus macaque colonies (Macaca mulatta and M. fascicularis) at the California Regional Primate Research Center. The computerized database used in this analysis included fetuses, term infants, juveniles, and adults that underwent a necropsy procedure over a 14-year period (1983-1996). The calculated malformation rates were 0.9% (40/4,390) and 0.3% (3/965) for the rhesus and cynomolgus monkey, respectively. Most of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 22 publications
3
26
0
Order By: Relevance
“…Lapin and Yakovleva (1963) reported similar results, with a 0.48% congenital malformation rate and one individual with CLMs (Morris, 1971). Hendrickx and Prahalada (1986) and Peterson et al (1997) each found 1 case of CLM in 1698 (0.06%) and 4390 (0.02%) necropsies, respectively, conducted on captive rhesus macaques at the California Regional Primate Center. Two subsequent cases of CLM were reported at the same facility (Brignolo et al, 2002).…”
Section: Introductionsupporting
confidence: 59%
“…Lapin and Yakovleva (1963) reported similar results, with a 0.48% congenital malformation rate and one individual with CLMs (Morris, 1971). Hendrickx and Prahalada (1986) and Peterson et al (1997) each found 1 case of CLM in 1698 (0.06%) and 4390 (0.02%) necropsies, respectively, conducted on captive rhesus macaques at the California Regional Primate Center. Two subsequent cases of CLM were reported at the same facility (Brignolo et al, 2002).…”
Section: Introductionsupporting
confidence: 59%
“…Because of the single births, low fertility rates, and high spontaneous abortion rates, enlarging the group sizes for these studies based on statistical power is not practical or appropriate. In spite of these limitations of the model, developmental toxicity studies in NHPs have provided a high level of predictivity of human teratogens (Schardein et al, 1985), perhaps related to the low background incidence of malformations in NHPs (Peterson et al, 1997). It should be recognized that the purpose of these studies is to identify the hazard, but they may not be appropriate for use in risk assessment.…”
Section: Current and Future Trends In Nhp Dartmentioning
confidence: 98%
“…To our knowledge, there has been only one previous case of conjoined twins reported in Old World macaques. This case involved cranial duplication in nonviable term rhesus monkey infants in our breeding colony [10].…”
Section: Discussionmentioning
confidence: 98%